A CARTOGRAFIA COMO PESQUISA-IN(TER)VENÇÃO DO/NO PRESENTE: modos de/para pensar-fazer a formação docente - Pocahy, Fernando; Gomes da Silva, Ana Lúcia; Oliveira Carvalho Dourado, Emanuela (Revista Ciências Humanas, 2020)
A CARTOGRAFIA COMO PESQUISA-IN(TER)VENÇÃO DO/NO PRESENTE